La dificultad de perdurar. Primeras experiencias periodísticas y asociativas en la provincia de Tucumán. 1820-1852. - Nanni, Facundo (Revista Territórios e Fronteiras, 2017)
Abstract:In the province of Tucumán during the period before the constitutional organization of the Rio de la Plata territory, the first associations and periodicals appeared despite their ephemeral nature and allowed to construct new areas for public discussion and political deliberation at a stage characterized by the "provisional autonomies", in which the provinces reassumed the sovereignty but establishing among themselves a series of pacts waiting for a future organization of the national territory.